Combine-Phytotoxic Effects of Polycyclic Aromatic Hydrocarbons on Sweet Corn (Zea mays L. var sacharata Bailey), Cowpea (Vigna sinensis) and Squash (Cucurbita moschata) - สมตระกูล ขนิษฐา; ไชยเมืองคูณ จำปี; ผลาผล ดวงอนงค์; ฉุยฉาย วราภรณ์ (KKU Science Journal, 2013)
The combine toxicity of fluorene and fluoranthene with phenanthrene or anthracene (1:1 ratio) to seedling growth of sweet corn (Zea mays L. var sacharata Bailey), cowpea (Vigna sinensis), and squash (Cucurbita moschata) were studied. The result shown that the most sensitive plant to PAH-combine toxicity was sweet corn, the moderate was cow pea, and the most tolerant species was squash. Root length and fresh weight of seedling was sensitive to PAH-combine toxicity. The combination of fluorene, fluoranthene and anthracene was toxic to plants more than the combination of fluorene, fluoranthene and phenanthrene.